Adalimumab-induced acute interstitial lung disease in a patient with rheumatoid arthritis - Olivia Meira Dias; Daniel Antunes Silva Pereira; Bruno Guedes Baldi; Andre Nathan Costa; Rodrigo Abensur Athanazio; Ronaldo Adib Kairalla; Carlos Roberto Ribeiro Carvalho (Jornal Brasileiro de Pneumologia, 2014)
The use of immunobiological agents for the treatment of autoimmune diseases is increasing in medical practice. Anti-TNF therapies have been increasingly used in refractory autoimmune diseases, especially rheumatoid arthritis, with promising results. However, the use of such therapies has been associated with an increased risk of developing other autoimmune diseases. In addition, the use of anti-TNF agents can cause pulmonary complications, such as reactivation of mycobacterial and fungal infections, as well as sarcoidosis and other interstitial lung diseases (ILDs). There is evidence of an association between ILD and the use of anti-TNF agents, etanercept and infliximab in particular. Adalimumab is the newest drug in this class, and some authors have suggested that its use might induce or exacerbate preexisting ILDs. In this study, we report the first case of acute ILD secondary to the use of adalimumab in Brazil, in a patient with rheumatoid arthritis and without a history of ILD.